Toyin Falola@65 Conference: African Knowledges and Alternative Futures - Amber Murrey; Edith Phaswana (Yoruba Studies Review)
The Toyin Falola @65 Conference brought together scholars from across the African continent and the world from 29 to 31 January 2018 under the theme, ‘African Knowledge and Alternative Futures.’ Our focus reflected on the long struggle for epistemic justice on the continent while centering and recognizing Falola’s important role in the project. This was a unique conference in terms of its structure, content, as well as the diversity of intellectuals that it attracted.